Unusual presentation of luminal breast carcinoma metastatic to the brain and coma: a case report of dramatic response to abemaciclib and literature review - Maria Rosaria Valerio; Calogero Cipolla; Martina Greco; Chiara Mesi; Francesca Modica; Vittorio Gebbia; Giuseppa Scandurra; Daniela Sambataro (Therapeutic Advances in Medical Oncology)
Patients with luminal breast cancer (BC) may develop central nervous system metastases in 20%–40% of cases. Radiation or surgical therapy represents the cornerstone of treating central nervous system metastases. Meanwhile, the best practice for metastatic luminal BC involves using cyclin-dependent kinase 4/6 inhibitors combined with endocrine therapy. To our knowledge, this is the first case to report a dramatic response of breast metastases to abemaciclib plus endocrine therapy without radiation therapy, particularly in a patient who presented with seizures and sudden coma. She received brain surgery to control a large bleeding metastasis. Abemaciclib was crushed and diluted in water for administration via the nasogastric tube, while an upfront fulvestrant was given since aromatase inhibitors cannot be diluted. Beyond the radiological response, the clinical improvement was notable, with complete symptom recovery to the point where she is again working. Our paper supports the activity of abemaciclib in brain metastases from luminal BC and includes a review of the medical literature. Further investigation is warranted in this clinical setting.